The Experience of Using Various Modalities For Orbital Floor Fracture Reconstruction - Prawoto, Pujisriyani; Handayani, Siti; Bangun, Kristaninta (Jurnal Plastik Rekonstruksi, 2012)
Background: Fractures of the orbital floor require surgical intervention in group of patients with cosmetic problems and/or vertical diplopia. The surgical management of these patients provides a great challenge to the surgeon. A variety of implant materials have been used to recreate normal bony orbital dimension or supplement deficient orbital volume which include alloplastic or autogenous materials. The purpose of this case series was to assess the aesthetic and functional outcome of orbital floor reconstruction performed with calvarial bone graft, titanium mesh, absorbable mesh and “Turkish Delight” diced cartilage graft.Patients and Methods: From 2006-2010, we treated eight patients with orbital blowout fracture using various modalities. We used titanium mesh, absorbable mesh, calvarial bone graft and “Turkish delight” diced cartilage. These various modalities were chosen based on clinical examination, patient satisfaction, radiographic investigations and the cost on managing patient.Result: Calvarial bone graft were performed in two patient, “Turkish delight” diced cartilage in one patient, absorbable mesh in one patient, and titanium mesh in four patient. All patients had satisfactory result with adequate volume correction and reduction in vertical diplopia.Summary: All four materials, calvarial graft, titanium mesh, absorbable mesh, and “Turkish delight” diced cartilage graft have the potential to be useful reconstructive materials in orbital floor blowout fractures based on holistic consideration.